Strategi Guru dalam Menangani Anak Speech Delay di Sekolah Dasar: Studi Kasus - Fitriyani Fitriyani; Liftiah Liftiah; Ali Formen (STKIP Subang, 2025)
This study was motivated by the existence of elementary school children who experience language development disorders, namely speech delay compared to their peers in the sixth grade of an elementary school in Cirebon City. The child, whose initials are D, experiences speech delay, which hinders his communication and learning processes. This study aims to determine the strategies and obstacles faced by Teacher Y in handling Child D, who experiences speech delay in elementary school. The research method used was qualitative research with a case study. The data collection techniques used were interviews and observation. The data analysis technique used was the Miles and Huberman Model. The results of the study showed that the strategies used by the teacher were multisensory, simple and gradual instruction, and the use of interactive learning media, methods, and models to stimulate the child's language. Meanwhile, the obstacles encountered were limited time for assistance, a lack of supporting facilities, and inconsistent stimulation at home. Based on these research results, it was concluded that handling children with speech delay requires varied strategies supported by collaboration between teachers and parents in order to achieve optimal results.